Extra-pulmonary tuberculosis in Saudi Arabia - Al-Otaibi Fawzia; El Hazmi Malak (Wolters Kluwer Medknow Publications, 2010)
Studies from developed countries have reported that extra-pulmonary tuberculosis (EPTB) is on the rise due to the human immunodeficiency virus (HIV) epidemic. However, similar studies from high-burden countries with low prevalence of HIV like Saudi Arabia are lacking. Therefore, we conducted this study to investigate demographic and clinical characteristics of patients with pulmonary and extra-pulmonary tuberculosis. A retrospective analysis was carried out on all patients (n=431) with a culture - proven diagnosis of tuberculosis seen at University teaching hospital, Riyadh, Saudi Arabia from January 2001 to December 2007. A total of 183 (42.5%) pulmonary tuberculosis (PTB) and 248 (57.5%) extra-pulmonary TB (EPTB) cases were compared in terms of age, sex, and nationality. There were 372 Saudis (SA) (86.3%) and the remaining non-Saudis (NSA) 59 (13.7%). The age distribution of the PTB patients had a bimodal distribution. EPTB was more common at young age (20-29 years). The proportion of EPTB cases was significantly higher among NSA patients (72.9%) compared to SA patients (55.1%). Females had higher proportion (59.5%) of EPTB than males (55.6%). The most common site was lymph node tuberculosis (42%). In conclusion, our data suggest that EPTB was relatively common in younger age, female gender and NSA. Tuberculosis (TB) control program may target those populations for EPTB case-finding.